“Does Institutional Quality, Natural Resources, Globalization, and Renewable Energy Contribute to Environmental Pollution in China? Role of Financialization” - Ameer, Waqar; Amin, Azka; Xu, Helian (Frontiers in Public Health, 2022)
Our study explores the impact of financialization on carbon emission by utilizing diverse financialization proxies, particularly for China. We examine the impact of financialization, institutional quality, globalization, natural resources, trade openness, renewable and nonrenewable energy consumption on environmental pollution over the period 1996-2017 by utilizing the dynamic ARDL simulations. The empirical findings of the study indicate that institutional quality, trade, globalization, natural resources, and renewable energy consumption significantly decrease environmental pollution in the long run, while foreign direct investment and financialization have neutral effects on carbon emission. Our findings demonstrate that 1% increase in institutional quality, trade, IFDI, renewable energy and globalization leads to decrease CO2 emissions by 0.198%, 0.016%, 0.075%, 0.010% and 0.072% respectively. Even though, financialization indexes contributed insignificantly to environmental degradation, other explanatory variables significantly affected carbon emission through indirect effects of financialization. Financialization indexes behave in a similar context, and these proxy indicators are good parameters to understand the complex nature of financialization. Moreover, in to order to achieve low carbon emissions and sustainable development, the countries need viable financial institutions that focus on green growth by promoting clean production process strategy to ensure the reduction of CO2 emissions.